Low-Dose Dexmedetomidine Accelerates Gastrointestinal Function Recovery in Patients Undergoing Lumbar Spinal Fusion - Meng Li; Meng Li; Tianlong Wang; Tianlong Wang; Wei Xiao; Wei Xiao; Lei Zhao; Lei Zhao; Dongxu Yao; Dongxu Yao (Frontiers Media S.A., 2019)
Background: Dexmedetomidine possesses sedative, sympatholytic, and opioid-sparing properties, but its impact on postoperative gastrointestinal function is controversial.Methods: This single-center, prospective, randomized study compared low-dose dexmedetomidine and placebo on gastrointestinal function recovery and inflammation after posterior lumbar spinal fusion. Sixty-six patients were randomized into two groups and received normal saline (control group) or dexmedetomidine (DEX group) during posterior lumbar fusion. Blood was taken at five timepoints to measure lipopolysaccharides, tumor necrosis factor-α, and C-reactive protein. The primary outcome was duration to first flatus. The secondary outcomes were inflammatory mediators and determination of correlations between perioperative factors and duration to first flatus.Results: Patients in DEX group showed significantly lower duration to first flatus (15.37 [13.35-17.38] vs 19.58 [17.31-21.86] h; p = 0.006) and overall sufentanil consumption (67.19 [63.78-70.62] vs 74.67 [69.96-79.30] μg; p = 0.011) than controls. Lipopolysaccharides, tumor necrosis factor-α, and C-reactive protein did not differ between the groups at any timepoint (all p > 0.05). Multiple linear regression modeling assessed the ability of independent variables to predict variance in duration to first flatus (adjusted R2 = 0.379, p = 0.000). In the model, age (β = 0.243, p = 0.003), gender (β = −3.718, p = 0.011), BMI (β = −0.913, p = 0.001), operative segments (β = −4.079, p = 0.028), and overall sufentanil consumption (β = 0.426, p = 0.000) contributed significantly.Conclusions: Thus, low-dose dexmedetomidine accelerates gastrointestinal function recovery after lumbar spinal fusion. The effect may be partially produced by opioid-sparing effects rather than inhibition of inflammation.Clinical Trial Registration:www.chictr.org.cn, identifier ChiCTR1800018127.